PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN BUDIDAYA LEBAH MADU KELE-KELE (TRIGONA Spp.) DI DESA BATUAN KALER, KECAMATAN SUKAWATI, GIANYAR - Gede Sidi Artajaya Sidi Artajaya; A.A. Istri Mirah Dharmadewi; Ni Ketut Erawati (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
Community empowerment is one of the important strategies in improving the social and economic welfare of the Batuan Kaler Village community. This study aims to develop the potential of the Batuan Kaler Village community, Sukawati District, Gianyar, through training in the cultivation of kele-kele honey bees (Trigona spp.). The training method involves a participatory approach that includes theoretical counseling, direct practice, and ongoing mentoring. Trigona spp. bees were chosen because of their simple maintenance, low cost, and honey production that has high economic value. The results of the activity showed an increase in community knowledge and skills in honey bee cultivation, as well as the potential for developing sustainable Trigona spp. honey-based micro-businesses. This program not only provides economic benefits but also contributes to environmental conservation through the sustainability of the bee ecosystem. This program is expected to provide further contributions and government support in developing markets for local honey products.